Back Cover. Issue 5 (11th September 2022) - Unknown
Abstract : Solar‐driven interfacial evaporation holds significant promise for vapor generation, seawater desalination, and wastewater treatment. However, salt accumulation is one of the key bottlenecks for reliable adoption. Li et. al. reported a bioinspired hierarchical evaporator inspired by the leaves‐on‐stems architecture in pristine plants, achieving efficient and durable evaporation in hypersaline water, offering insights into the structural design of next‐generation solar evaporators. Abstract : Solar‐driven interfacial evaporation holds significant promise for vapor generation, seawater desalination, and wastewater treatment. However, salt accumulation is one of the key bottlenecks for reliable adoption. Li et. al. reported a bioinspired hierarchical evaporator inspired by the leaves‐on‐stems architecture in pristine plants, achieving efficient and durable evaporation in hypersaline water, offering insights into the structural design of next‐generation solar evaporators.